Finger Gesture Detection Experiment using Software Defined Radio Radar - Edwar, Edwar; Ali, Erfansyah; Feriska, Rizkia; Muzzaki, Ikhwan (Jurusan Teknik Elektro UIN Sunan Gunung Djati Bandung, 2023)
Human gesture detection for Human to Machine (H2M) Communication is usually done by using a camera. However, this device has a dependency of light illumination. To overcome this limitation, a radar can be utilized to read the finger gesture because it uses electromagnetic wave that is independent of the light appereance. Radar device is usually complicated and consists of components. In this research, a Software Defined Radio (SDR) was used to simplify the radar device circuit. The SDR generated the continuous wave (CW) signal that is suitable for detecting moving object such as finger gesture. The radar was working on 2.4 GHz of frequency. The results of the CW radar system using SDR shows that each gesture has a different reflected signal pattern, amplitude, and phases so we can conclude that each gesture has a character that can be distinguished through the characterization of reflected electromagnetic waves. This promising result can be the future application such as H2M) communication.